Cerebrovascular accidents in paediatric patients supported by the Berlin Heart EXCOR. (18th July 2022) - Rohde, Sofie; Sandica, Eugen; Veen, Kevin; Miera, Oliver; Amodeo, Antonio; Napoleone, Carlo Pace; Özbaran, Mustafa; Sliwka, Joanna; Thiruchelvam, Timothy; Zimpfer, Daniel; Schubert, Stephan; Bogers, Ad J J C; et al.
Abstract: OBJECTIVES: Ventricular assist device support as a bridge to transplant or recovery is a well-established therapy in children on the cardiac transplant waiting list. The goal of this study was to investigate the incidence of and the associated factors for cerebrovascular accidents in paediatric patients supported by a Berlin Heart EXCOR. METHODS: All patients <19 years of age supported by a Berlin Heart EXCOR between January 2011 and January 2021 from the European Registry for Patients with Mechanical Circulatory Support were included. RESULTS: In total, 230 patients were included. A total of 140 (60.9%) patients had a diagnosis of dilated cardiomyopathy. 46 patients (20.0%) sustained 55 cerebrovascular accidents, with 70.9% of the episodes within 90 days after the ventricular assist device was implanted. The event rate of cerebrovascular accidents was highest in the first era (0.75). Pump thrombosis and secondary need for a right ventricular assist device were found to be associated with a cerebrovascular accident (hazard ratio 1.998, P  = 0.040; hazard ratio 11.300, P  = 0.037). At the 1-year follow-up, 44.4% of the patients had received a transplant, 13.1% were weaned after recovery and 24.5% had died. Event rates for mortality showed a significantly decreasing trend. CONCLUSIONS: Paediatric ventricular assist device support is associated with important adverse events, especially in the early phase after the device is implanted. Pump thrombosis and the need for a secondary right ventricular assist device are associated with cerebrovascular accidents. Furthermore, an encouragingly high rate of recovery in this patient population was shown, and death rates declined. More complete input of data into the registry, especially concerning anticoagulation protocols, would improve the data. Abstract : Ventricular assist devices (VAD) have become an important aspect in the treatment of children with end-stage heart failure and often act as a last resort for these severely sick children awaiting a cardiac transplant.